Efforts to Improve Student Learning Outcomes in Islamic Education Learning through the Sharing Model and Audio Visual Media at Ie Seuum State Elementary School - Rosnawati; Marlina (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the effectiveness of the application of the Sharing Model and the use of Audio-Visual Media in improving student learning outcomes in Islamic Religious Education subjects. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were 5th grade students of Neferi Ie Seeum Elementary School. The data of this study were obtained through systematic observation, evaluation, and reflection, teachers can adjust their teaching methods to better suit students' needs. The iterative nature of CAR allows for continuous improvement in the learning process. The data analysis technique used in this study is quantitative Pre Experiment Design in the form of One Group Pretest and Posttest Design. The results of the study indicate that an interactive and multimedia-based learning approach creates a more dynamic classroom environment, thereby improving students' understanding and retention of material.